Multilevel hiding text security using hybrid technique steganography and cryptography - Hassoon, Noor Hasan; Ali, Rajaa Ahmed; Abed, Hazim Noman; Alkhazraji, Adel Abdul-Jabbar (International Journal of Engineering and Technology, 2026)
Information security in the recent decades has become one of the main topics in communication systems. Security of information de-pended on strength of the keys in the Cryptographic and Steganographic processes. In this paper, a few techniques are used to implement both steganography and cryptography. The process of hiding data in this research goes through several processes, as follows: the first process is to encrypt a secret message through the use of Blowfish algorithm to generate the key that will be used in the encryption process and XOR it with a secret message. The second process, hiding positions are determined by using the edge detection algorithm to a cover image. After that, the bats algorithm will be applied to the cover image resulted by edge detection to choose random hiding positions in edge detection image. The last stage is to embed the secret message in a cover image using the least significant bit. Fig2 shows the opera-tions achieved on the secret message.